(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
In Algeria, forest ecosystems bring together a diversity of fungal species and little data is currently available on forest macrofungi. This preliminary study focuses on the distribution and ecology of macrofungi in two sites in Northwester of Algeria. The mycological surveys carried out for the first time during two successive years made it possible to determine the fungal and floristic diversity as well as the climatic parameters and the physicochemical characteristics of the soil. The results indicate a good relation between the appearance of fungi and environmental factors. The fungal inventory carried out in the two study sites reveals a diversity of macrofungi comprising 44 taxa (84.09% basidiomycetes and 15.9% ascomycetes) distributed in 24 genera and 17 families. This diversity of the macrofungi identified is also linked to the density of the plant cover made up of three strata: tree, shrub and herbaceous. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 33-46